2006
DOI: 10.1099/mic.0.2006/000315-0
|View full text |Cite
|
Sign up to set email alerts
|

Topology of the outer-membrane secretin PilQ from Neisseria meningitidis

Abstract: Neisseria meningitidis is the causative agent of epidemic meningococcal meningitis and septicaemia. Type IV pili are surface organelles that mediate a variety of functions, including adhesion, twitching motility, and competence for DNA binding and uptake in transformation. The secretin PilQ is required for type IV pilus expression at the cell surface, and forms a dodecameric cage-like macromolecular complex in the meningococcal outer membrane. PilQ-null mutants are devoid of surface pili, and prevailing eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 56 publications
3
32
0
Order By: Relevance
“…The presence of intact pili on M1M2 suggests that enough disulphidebonded PilQ is formed to produce the secretin without DsbA-catalysed folding, but it may be that the function of the pore or a separable PilQ activity in DNA binding and uptake is affected more profoundly. These findings are also in agreement with the recent discovery that the PilQ complex binds DNA in the core of its central channel (Assalkhou et al, 2007;Frye et al, 2006), explaining why DNA binding and uptake are reduced in the DsbA1/2 mutant. Assalkou et al (2007) showed that PilQ bound DNA irrespective of the presence of DUS, which was confirmed in our assays, as binding of plasmid DNA with and without DUS was comparably reduced in M1M2.…”
Section: Discussionsupporting
confidence: 81%
“…The presence of intact pili on M1M2 suggests that enough disulphidebonded PilQ is formed to produce the secretin without DsbA-catalysed folding, but it may be that the function of the pore or a separable PilQ activity in DNA binding and uptake is affected more profoundly. These findings are also in agreement with the recent discovery that the PilQ complex binds DNA in the core of its central channel (Assalkhou et al, 2007;Frye et al, 2006), explaining why DNA binding and uptake are reduced in the DsbA1/2 mutant. Assalkou et al (2007) showed that PilQ bound DNA irrespective of the presence of DUS, which was confirmed in our assays, as binding of plasmid DNA with and without DUS was comparably reduced in M1M2.…”
Section: Discussionsupporting
confidence: 81%
“…Within the complex is a long tapered cavity that is 90 Å in height, and 87 Å in diameter at its broadest point. The topology of the PilQ complex was investigated using insertion epitopes and immunogold labelling [40]. These studies showed that both the N-terminal and C-terminal regions of PilQ localize to the periplasm, including an insert at residue 205, which maps to the arms of the complex.…”
Section: The Outer Membrane Secretinmentioning
confidence: 99%
“…Within the complex is a long tapered cavity that is 90 Å in height, and 87 Å in diameter at its broadest point. The topology of the PilQ complex was investigated using insertion epitopes and immunogold labelling [40]. These…”
Section: The Outer Membrane Secretinmentioning
confidence: 99%
“…2A). As has been done to investigate various types of OM proteins, including other iron transporters (22,23,50,89,106,122,127,130), we introduced a His 6 -tagged version of LbtU into 130b and then used anti-His antibodies and immunoblot analysis to track the location of LbtU in cellular fractions. LbtU-His 6 did not diminish the growth of the wild type and complemented an iron-related growth defect of an lbtU mutant (see below, Fig.…”
Section: Vol 193 2011mentioning
confidence: 99%